2021
DOI: 10.12688/wellcomeopenres.16584.2
|View full text |Cite
|
Sign up to set email alerts
|

­­­­­­­A type I IFN, prothrombotic hyperinflammatory neutrophil signature is distinct for COVID-19 ARDS­­­

Abstract: Background: Acute respiratory distress syndrome (ARDS) is a severe critical condition with a high mortality that is currently in focus given that it is associated with mortality caused by coronavirus disease 2019 (COVID-19). Neutrophils play a key role in the lung injury characteristic of non-COVID-19 ARDS and there is also accumulating evidence of neutrophil mediated lung injury in patients who succumb to infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods: We undertook a func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 53 publications
9
42
0
Order By: Relevance
“…In particular, we found that dexamethasone treatment did not modulate the functional landscape of neutrophils or attenuate the production of NETs. This is in line with a publication suggesting that dexamethasone does not alter the NET-related neutrophil proteome in patients with severe COVID-19 ( 28 ). Of note, our findings do not rule out the possibility that dexamethasone modulates other aspects of neutrophil development or activation in vivo, as has been suggested using transcriptomic analysis of the circulating neutrophil pool in severe COVID-19 ( 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…In particular, we found that dexamethasone treatment did not modulate the functional landscape of neutrophils or attenuate the production of NETs. This is in line with a publication suggesting that dexamethasone does not alter the NET-related neutrophil proteome in patients with severe COVID-19 ( 28 ). Of note, our findings do not rule out the possibility that dexamethasone modulates other aspects of neutrophil development or activation in vivo, as has been suggested using transcriptomic analysis of the circulating neutrophil pool in severe COVID-19 ( 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…Neutrophil characterization by transcriptional and proteomic analysis in COVID-19 indicates significant heterogeneity among mature neutrophils and emergence of a large number of low density neutrophils (LDN) with multiple phenotypes ( 16 , 24 , 25 , 27 30 ). The functional capability of these various neutrophil populations has been inferred from gene or protein expression profiles ( 22 26 ), however, previous direct functional studies either did not evaluate the various neutrophil populations or disparate results were reported ( 12 15 , 24 , 28 37 ). Thus, the functional heterogeneity among the various neutrophil populations remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…The increased glycolytic activity of COVID-19 neutrophils might provide a mechanistic explanation for the increased spontaneous NET formation by neutrophils isolated from patients with severe COVID-19 (209,210). However, contrasting results have also been reported that suggested an impaired glycolytic flow and oxidative metabolism in neutrophils isolated from COVID-19 patients with ARDS symptoms (223). Currently, the reasons for these different findings remain unclear.…”
Section: Covid-19mentioning
confidence: 99%